Cellular Tolerance Induced by Chronic Opioids in the Central Nervous System - Adhikary, Sweta; Williams, John T. (Frontiers in Systems Neuroscience, 2022)
Opioids are powerful analgesics that elicit acute antinociceptive effects through their action the mu opioid receptor (MOR). However opioids are ineffective for chronic pain management, in part because continuous activation of MORs induces adaptive changes at the receptor level and downstream signaling molecules. These adaptations include a decrease in receptor-effector coupling and changes to second messenger systems that can counteract the persistent activation of MORs by opioid agonists. Homeostatic regulation of MORs and downstream signaling cascades are viewed as precursors to developing tolerance. However, despite numerous studies identifying crucial mechanisms that contribute to opioid tolerance, no single regulatory mechanism that governs tolerance in at the cellular and systems level has been identified. Opioid tolerance is a multifaceted process that involves both individual neurons that contain MORs and neuronal circuits that undergo adaptations following continuous MOR activation. The most proximal event is the agonist/receptor interaction leading to acute cellular actions. This review discusses our understanding of mechanisms that mediate cellular tolerance after chronic opioid treatment that, in part, is mediated by agonist/receptor interaction acutely.